Electronic Controlling on Nanotribological Properties of a Textured Surface by Laser Processing - Haifeng Yang; Kun Liu; Yanqing Wang; Hao Liu; Jiaxiang Man; Bo Sun (Journal of Spectroscopy)
The friction-reducing performance of surfaces with regular nanotextures is a key topic in surface engineering research. This paper presented a simple, easily controlled method for fabricating regular nanotextures on an electrodeposited Ni-Co alloy. The electronic controlling on the friction performance of a nanotexured surface was investigated by AFM. The results showed that the frictional force of a nanotexured surface can be controlled by an external electric field. Before laser processing, the friction initially increased with the bias voltage and then decreased after the bias voltage exceeded 1.0 V. Its friction forces can be changed more than 2 times under the different external electric field. After laser processing, the trend of the frictional force was reversed and its friction forces changed more than 12 times for the laser-processed sample with 0.18 J/cm2 laser power. The results also showed that the friction force decreased when using different nanotextures in an external electric field.